Language Complexity, Narratives and Theory of Mind of Romani Speaking Children - Hristo Kyuchukov; Jill de Villiers (East European Journal of Psycholinguistics, 2018)
The paper presents research findings with 56 Roma children from Macedonia and Serbia between the ages of 3-6 years. The children’s knowledge of Romani as their mother tongue was assessed with a specially designed test. The test measures the children’s comprehension and production of different types of grammatical knowledge such as wh–questions, wh-complements, passive verbs, possessives, tense, aspect, the ability of the children to learn new nouns and new adjectives, and repetition of sentences. In addition, two pictured narratives about Theory of Mind were given to the children. The hypothesis of the authors was that knowledge of the complex grammatical categories by children will help them to understand better the Theory of Mind stories. The results show that Roma children by the age of 5 know most of the grammatical categories in their mother tongue and most of them understand Theory of Mind.ReferencesBakalar, P. (2004). The IQ of Gypsies in Central Europe. The Mankind Quarterly, XLIV, (3&4), 291-300.Bedore L.M., Peña E.D., García, M. & Cortez, C. (2012). Conceptual versus monolingual scoring: when does it make a difference? J Speech Lang Hear Res 55(1), 1-15.Berko, J. (1958). The Child's Learning of English Morphology. Word 14, 150-177.Berman, R. & Slobin, D. (2009). Relating Events in Narrative: A Cross-Linguistic developmental Study, vol. 1. New York and London: Psychology Press.Bialystok, E. (2001). Bilingualism in development: Language literacy and cognition. Cambridge University Press: Cambridge.Bialystok, E. & Craik, F. (2010). Cognitive and Linguistic processing in the bilingual mind. Current Directions in Psychological Science, 19, (1), 19-23.Bialystok, E., Craik, F., and Freedman, M. (2007). Bilingualism as a protection against the onset of symptoms of dementia. Neuropsychologia, 45, 459-464.Brucker, J. L. (n.d). A study of Barriers to Educational Attainment in the Former Yugoslav Republic of Macedonia. www.unicef.org/ceecis/Roma_children.pdfBruner, J. (1986). Actual mind, possible worlds. Cambridge: Harvard University Press.Carlson, S. & Meltzoff, A. (2008). Bilingual Experience and Executive Functioning. Bilingualism: Language and Cognition, 6 (1), 1-15.Chen, C. & Stevenson. H. (1988). Cross-Linguistic Differences in Digit Span of Preschool Children. Journal of Experimental Child Psychology 46, 150-158Conti-Ramsden, S., Botting, N. & Faragher, B. (2001). Psycholinguistic Marker for specific Language Impairment (SLI). Journal of Language Psychology and Psychiatry, 42 (6), 741-748.Curenton, S. M. (2004). The association between narratives and theory of mind for low-income preschoolers. Early Education and Development, 15 (2), 120–143.Deen, Kamil Ud (2011). The Acquisition of the Passive. In de Villiers, J. & T. Roeper. (eds) Handbook of Generative Approaches to Language Acquisition (pp. 155-188). Amsterdam: John Benjamins Publisher.de Villiers, J., Pace, A., Yust, P., Takahesu Tabori, A., Hirsh-Pasek, K., Golinkoff, R. M., Iglesias, A., & Wilson, M.S. (2014). Predictive value of language processes and products for identifying language delays. Poster accepted to the Symposium on Research in Child Language Disorders, Madison, WI.de Villiers, J. G. (2015). Taking Account of Both Languages in the Assessment of Dual Language Learners. In Iglesias, A. (Ed) Special issue, Seminars in Speech, 36 (2) 120-132.de Villiers, J. G. (2005). Can language acquisition give children a point of view? In J. Astington & J. Baird (Eds.), Why Language Matters for Theory of Mind. (pp186-219) New York: Oxford Press.de Villiers J. G. & Pyers, J. (2002). Complements to Cognition: A Longitudinal Study of the Relationship between Complex Syntax and False-Belief Understanding. Cognitive Development, 17: 1037-1060.de Villiers, J. G., Roeper, T., Bland-Stewart, L. & Pearson, B. (2008). Answering hard questions: wh-movement across dialects and disorder. Applied Psycholinguistics, 29: 67-103.Friedman, E., Gallová Kriglerová, E., Kubánová, M. & Slosiarik, M. (2009). School as Ghetto: Systemic Overrepresentation of Roma in Special Education in Slovakia. Roma Education Fund.ERRC (European Roma Rights Center) (1999). A special remedy: Roma and Special schools for the Mentally Handicapped in the Czech Republic. Country Reports Series no. 8 (June)ERRC (European Roma Rights Centre) (2014). Overcoming barriers: Ensuring that the Roma children are fully engaged and achieving in education. The office for standards in education. online at http://www.errc.orgERRC (European Roma Rights Centre) (2015). Czech Republic: Eight years after the D.H. judgment a comprehensive desegregation of schools must take place http://www.errc.orgFremlova, L. & Ureche, H. (2011). From Segregation to Inclusion: Roma pupils in the United Kingdom. A Pilot research Project. Budapest: Roma Education Fund.Gleitman, L., Cassidy, K., Nappa, R., Papafragou, A. & Trueswell, J. (2005). Hard words. Language Learning and Development, 1, 23-64.Goetz, P. (2003). The effects of bilingualism on theory of mind development. Bilingualism: Language and Cognition. 6. 1-15.Hart, B. & Risley, T.R (1995). Meaningful Differences in the Everyday Experiences of Young American Children. Baltimore, MD: Brookes PublishingHeath, S. B. (1982). What no Bedtime Story Means: Narrative skills at home and at school. In Language and Society. 11.2:49-76.Hirsh-Pasek, K., Kochanoff, A., Newcombe, N. & de Villiers, J.G. (2005). Using scientific knowledge to inform preschool assessment: making the case for empirical validity. Social Policy report (SRCD) Volume XIX, 1, 3-19.Hirsh-Pasek K., Adamson, I.B., Bakeman, R., Tresch Owen, M., Golinkoff, R.M., Pace, A., Yust, P & Suma, K. (2015). The Contribution of Early Communication Quality to Low- Income Children’s Language Success. Psychological Science Online First, June 5, 2015 doi:10.1177/0956797615581493Hoff, E. (2013). Interpreting the early language trajectories of children from low-SES and language minority homes: implications for closing achievement gaps. Developmental Psychology, 49(1):4-14.Hoff, E. & Elledge, C. (2006). Bilingualism as One of Many Environmental Variables that Affect Language Development in Young Children. In J. Cohen, K. McAlister & J. MacSwan (Eds.), Proceedings of the 4th International symposium on Bilingualism (pp. 1034-1040). Somerville, Ma: Cascadilla press.Hoge, W. (1998). A Swedish Dilemma: The Immigrant Ghetto. The New York Times, October 6th.Kovacs, A. (2009). Early Bilingualism Enhances Mechanisms of False-Belief Reasoning. Developmental Science, 12 (1), 48-54.Kyuchukov, H. (2005). Early socialization of Roma children in Bulgaria. In: X. P. Rodriguez-Yanez, A. M. Lorenzo Suarez & F. Ramallo (Eds.), Bilingualism and Education: From the Family to the School. Muenchen: Lincom Europa. (pp. 161-168)Kyuchukov, H. (2010) Romani language competence. In: J. Balvin and L. Kwadrants (Eds.), Situation of Roma Minority in Czech, Hungary, Poland and Slovakia (pp. 427-465). Wroclaw: Prom.Kyuchukov, H. (2014). Acquisition of Romani in a Bilingual Context. Psychology of Language and Communication, vol. 18 (3), 211-225.Kyuchukov, H. (2013). Romani language education and identity among the Roma children in European context. In: J. Balvin, L. Kwadrans and H. Kyuchukov (eds) Roma in Visegrad Countries: History, Culture, Social Integration, Social work and Education (pp. 465-471). Wroclaw: Prom.Kyuchukov, H. (2015). Socialization of Roma children through Roma oral culture. In: Socializaciya rastushego cheloveka v kontekste progressyivnyih nauchnich ideii XXI veka: socialnoe razvitie detey doshkolnogo vozrastta. [Socialization of the growing man in the context of progressive ideas of the XXI c.: social development of the preschool age children] Proceedings form the First international All-Russia conference, 1-3 April, Yakutsk, pp. 798-802.Kyuchukov, H. & de Villiers, J. (2009). Theory of Mind and Evidentiality in Romani-Bulgarian Bilingual children. Psychology of Language and Communication, 13(2), 21-34.Kyuchukov, H. & de Villiers, J. (2014a). Roma children’s knowledge on Romani. Journal of Psycholinguistics, 19, 58-65.Kyuchukov, H. & de Villiers, J. (2014b). Addressing the rights of Roma children for a language assessment in their native language of Romani. Poster presented at the 35th Annual Symposium on Research in Child Language Disorders in Madison, Wisconsin June 12-14.Lajčakova, J. (2013). Civil Society Monitoring Report on the Implementation of the National Roma Integration Strategy and Roma Decade Action Plan in 2012 in Slovakia. Budapest: Decade of Roma Inclusion. Secretariat Foundation.Landry, S. and the School Readiness Research Consortium (2014). Enhancing Early Child Care Quality and Learning for Toddlers at Risk: The Responsive Early Childhood Program. Developmental Psychology, 50 (2), 526-541.Lust, B., Flynn, S. & Foley, C. (1996). What Children Know about What They Say: Elicited Imitation as a Research Method for Assessing Children's Syntax. In D. McDaniel, C. McKee, & H. Smith Cairns (Eds.), Methods for Assessing Children's Syntax (pp. 55-76). Cambridge, Mass.: MIT Press.Maratsos, M., Fox, D.E.C., Becker, J.A. & Chalkley, M.A. (1985). Semantic restrictions on children’s passives. Cognition, 19, 167-191.Merz, E.C. Zucker, T.A., Landry, S.H. Williams, J., Assel, M., Taylor, H.B, Lonigan, C.L., Phillips, B., Clancy-Menchetti, J., Barnes, M., Eisenberg, N., de Villiers, J. (2015). Parenting predictors of cognitive skills and emotion knowledge in socioeconomically disadvantaged preschoolers. Journal of Experimental Child Psychology 132, 14-31Pearson, B. Z., Jackson, J. E., & Wu, H. (2014). Seeking a valid gold standard for an innovative dialect-neutral language test. Journal of Speech-Language and Hearing Research. 57(2). 495-508.Reger, Z. (1999). Teasing in the linguistic socialization of Gypsy children in Hungary. Acta Linguistica Hungarica, 46, 289-315.Réger, Z. and Berko-Gleason, J. (1991). Romāni Child-Directed Speech and Children's Language among Gypsies in Hungary Language in Society, 20 (4), 601-617.Roeper, T & de Villiers, J.G. (2011). The acquisition path for wh-questions. In de Villiers, J.G. & Roeper, T. (Eds), Handbook of Generative Approaches to Language Acquisition. Springer.Seymour, H., Roeper, T. & de Villiers, J. (2005). The DELV-NR. (Norm-referenced version) The Diagnostic Evaluation of Language Variation. The Psychological Corporation, San Antonio.Schulz, P. & Roeper, T. (2011). Acquisition of exhaustively in wh-questions: a semantic dimensions of SLI. Lingua, 121(3), 383-407.Stokes, S. F., Wong, A. M-Y., Fletcher, P., & Leonard, L. B. (2006). Nonword repetition and sentence repetition as clinical markers of SLI: The case of Cantonese. Journal of Speech, Language and Hearing Research, 49(2), 219-236.Vassilev, R. (2004). The Roma of Bulgaria: A Pariah Minority. The Global Review of Ethnopolitics, 3 (2), 40-51.Wellman, H.M., Cross, D., & Watson, J. (2001). Meta-analysis of theory-of-mind development: The truth about false belief. Child Development, 72, 655-684.Wimmer, H., & Perner, J. (1983). Beliefs about beliefs: Representation and constraining function of wrong beliefs in young children’s understanding of deception. Cognition, 13, 103–128.